Izzivi kadrovskega managementa v XXI. stoletju (University of Maribor Press, 2021)
Challenges of Human Resources Management in XXI. Century Marko Ferjan deals with phenomena: job satisfaction, organizational climate and work engagement. The concept of job satisfaction stems from the paradigm of organizational behavior. At the end of the 20th century, it already seemed, that the concept of job satisfaction was no longer relevant. Recently, however, measuring job satisfaction in conjunction with work engagement has become relevant again. Iztok Podbregar, Antonia Novak and Polona Šprajc discuss the recognition, promotion and inclusion of diversity of talents. In her article, Eva Jereb gives the characteristics of the currently most represented generations in jobs in organizations. Vesna Novak discusses the prevalence of precarious work. intended for the consequences of precariousness. Eva Jereb and Marko Urh deal with change and transition in times of crisis and the role of organizational leadership at this.